2009
DOI: 10.1103/physrevb.80.155128
|View full text |Cite
|
Sign up to set email alerts
|

Resonant coherent three-photon photoemission from Cu(001)

Abstract: We demonstrate the contribution of coherent excitation pathways in three-photon photoemission from Cu͑001͒. We identify separate peaks in the photoelectron spectra as originating from two specific Cu d bands that are excited at different k points via the same unoccupied image-potential state. By model calculations we show that our experimental observations impose lower limits on the relevant Cu d-hole dephasing time on the order of 10-20 fs. Our findings suggest extensions to future studies in electronic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…This is contrary to perturbative mPP spectra of metals, where single electrons absorb m photons from the occupied bands so the maximum photoelectron energy appears at E F þ mhν. Moreover, if multiple orders of m appear in mPP spectra, the photoelectron yield strongly decreases with each higher order [68,69]. The increase of m with decreasing hν can be understood in the following way.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is contrary to perturbative mPP spectra of metals, where single electrons absorb m photons from the occupied bands so the maximum photoelectron energy appears at E F þ mhν. Moreover, if multiple orders of m appear in mPP spectra, the photoelectron yield strongly decreases with each higher order [68,69]. The increase of m with decreasing hν can be understood in the following way.…”
Section: Resultsmentioning
confidence: 99%
“…In ultrafast photoelectron imaging experiments using 10-100 times higher fluences, thermionic photoemission from graphite with T e that saturates at 18,000 K has already been deduced, but its origin has not been discussed [89]. In light of typical mPP spectra of metals, where dipole transitions rather than energy and momentum scattering play the dominant role in the photoemission process [68,69], the rapid thermalization in graphite raises the question of the mechanism for the nonlinear electron excitation in graphite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that exchange effects between d electrons and 3s, 3p core states play a key role and cannot be neglected in the calculation of the QP corrections. Winkelmann et al [14] reported the clear influence of coherent excitation pathways in three-photon photoemission from copper (001).…”
Section: Introductionmentioning
confidence: 99%
“…We exclude three-photon photoemission (3PPE) due to insufficiently high excitation power densities, as considerably larger pulse fluences would be needed for 3PPE to occur. 32,33 Since for the chosen range of photon energies all levels available to electronic excitation from the valence band are below E F and thus already occupied, resonant 3PPE processes are excluded as well. The experimental conditions prevent thus photoemission from occupied valence band states.…”
Section: (B) Spectroscopy Inside the Gapmentioning
confidence: 99%